2020
DOI: 10.1097/ceh.0000000000000303
|View full text |Cite
|
Sign up to set email alerts
|

Digitalization and Physician Learning

Abstract: Supplemental Digital Content is Available in the Text.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 54 publications
1
6
0
Order By: Relevance
“…The study's results revealed that the core mission of the managers' professions had been shifted from tasks that were central before, such as being a coaching leader with a "hands-on" approach to leadership, into more digitally manageable tasks with increasingly administrative features. This finding is seen in previous studies, which indicate that some healthcare professions might experience digitalisation-related changes in their original professional core missions (Vallo Hult et al, 2020). This study revealed that increased digitalisation within a workplace might affect managers' health.…”
Section: Discussionsupporting
confidence: 84%
“…The study's results revealed that the core mission of the managers' professions had been shifted from tasks that were central before, such as being a coaching leader with a "hands-on" approach to leadership, into more digitally manageable tasks with increasingly administrative features. This finding is seen in previous studies, which indicate that some healthcare professions might experience digitalisation-related changes in their original professional core missions (Vallo Hult et al, 2020). This study revealed that increased digitalisation within a workplace might affect managers' health.…”
Section: Discussionsupporting
confidence: 84%
“…This evidence adds to a growing body of work understanding the relationships between healthcare technology use, competence and adoption by healthcare professionals. Recent work by Vallo et al [ 30 ] indicates that adoption and use of digital technology are “related to perceived performance, social influence and organisational context” and the role of ICT [Information and Communication Technology] in clinical professional development. This work highlights the need for a holistic service design approach [ 31 ] to reduce external and internal barriers to adoption and optimise the benefits and professional competence of use of these technologies in practice [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…Institutions aiming to adopt AI-CDSSs can leverage the important role of social influence by establishing a culture that values technological advancements and by engaging key opinion leaders to advocate and exemplify the use of these systems. Additionally, trainings can be structured not only to educate but also to establish a shared understanding and a community of practice that positively reinforces the application of AI-CDSSs [109,110]. By addressing the social aspects of technology acceptance, healthcare institutions can ensure that their investment in AI is met with a user base that is both competent and willing to integrate these tools into their daily practice.…”
Section: Practical Implicationsmentioning
confidence: 99%